Valores de referencia de elementos inorgânicos potencialmente tóxicos em solos do Estado de São Paulo - Consonni, João Luiz (2015)
The use of guiding values has been the practice in countries with tradition in monitoring the quality of natural resources. The first step of a pollution monitoring program is to establish the natural concentrations of potentially toxic elements (PTEs) in uncontaminated soil to the development of background values. Mean values of total PTE concentration in worldwide are very heterogeneous and resulting from different soils, extraction methods and techniques of analytical determination. The background values recommended by CETESB were obtained from samples of 13 soils, submitted to USEPA SW 846 3050 protocol, whose PTE contents were determined by atomic absorption spectrometry. The objective of this work was to contribute to the improvement of background values of Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, V and Zn in tropical soils, using topsoil samples (0-20 cm) of 30 representative soils of State of São Paulo, Brazil, collected in areas without human disturbance. The soil samples were submitted to the USEPA SW 846 3051, 3051 A and 3052 protocols, with microwaveassisted acid digestion. Natural contents of PTEs were determined by inductively coupled plasma optical emission spectrometry (ICP OES). Extraction protocols were evaluated using the certified soil sample NIST SRM 2709 San Joaquin. Arithmetic means were adopted to describe the central tendency and the variation of results from the different acid digestions and to set the background values into 75 and 90 percentiles. Regardless the extraction method, the average contents of EPT were in the following range of variation (mg kg-1): Al - 27118-42865; Ba - 78-101; Fe - 6318- 35888; Cd - ND - 2.2; Co - 18 to 37; Cr - 39-59; Cu - 43-61; Mn - 176-623; Ni - ND - 61; V - 111-193 and Zn - 63 to 68. The contents of Al, Co, Cu, Fe, Mn, V and Zn correlated with clay, amorphous (Feox) and crystalline (FeDCB) iron oxides contents. The method 3052 resulted in PTEs recovery levels within the limits considered acceptable for certified sample. Within recommended methods by CONAMA Resolution n.420 / 2009, the 3051 A was the best correlated with the method 3052 and was considered the protocol with high potential to improve soil background values. The new soil background values were (mg kg-1): a) percentile 75: Al - 66,700; BA - 68; CD - 1.53; Co - 16; Cr - 47; Cu - 20; Fe - 24,830; Mn - 333; Ni - 57; V - 66; Zn - 61; percentile 90: Al - 99 820; Ba - 113; CD - 1.78; Co - 30; Cr - 62; Cu - 32; Fe - 39 280; Mn - 480; Ni - 113; V - 119; Zn - 65. Since new background values differed from those currently practiced by CETESB, the use of ICP OES to determine natural PTE levels extracted by USEPA 3051 A, from a larger and more representative set of soils, supported the improvement of background values and may contribute to the improvement of the environmental risk assessment estimates for edaphoclimatical conditions of the State of São Paulo.